Authorship for interdisciplinary research: Who should be the first author? - Pradnya Kakodkar; Ramesh Bhonde (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Background: Authorship disputes are not rare when it is interdisciplinary research involving multiple researchers from different disciplines. Aim: The aim of this artilce is to recommend authorship guidelines for interdisciplinary research through a review of literature. Materials and Methods: Literature was searched using the search terms “Interdisciplinary research” and “authorship” in Medline since 2000–2020 and using Google. The literature was read and compiled. Based on the available literature suggestions and the present-day journal guidelines, recommendations are proposed. Results: Twelve unique and relevant articles were selected. They were read thoroughly, and four suggestions for determining authorship in interdisciplinary research are hereby proposed: (1) according to the International Committee of Medical Journal Editors; (2) group authorship; (3) contributor role taxonomy with 1000-point system; and (4) co-first authorship. Conclusion: Interdisciplinary team to harmoniously prepare the author list using the proposed suggestions and sort it at the initial planning stages before undertaking the work to avoid displeasure at the end.